Kids of knowledge what intervene in teaching practice (Praxis Educativa, 2012)
In order to analyze the different kinds of knowledge that teachers draw on to carry out their profession, it is necessary to expound and debate about the nature of such kinds of knowledge, despite the increasing evidence of their complexity and multi-determined nature that results from the various research studies. The purpose of this paper is to present a study carried out with university teaching trainee students. The conceptual ideas that these students have built during their university studies about the different kinds of knowledge that intervene in the teaching practice are analyzed in this study. This study begins with certain concepts that guided the development of the above mentioned experience. Next, the characteristics and methodological aspects underlying the study are described. Then, the characteristics of the teaching practice as wefi as the different kinds of knowledge to which the teacher resorts are analyzed. Finally, some reflections are outlined, which will sen/e as points of discussion for future analyses.
Keywords: knowledge; teaching practice; reflection; social construction; professionalism